Annual session of the Parliamentary Conference on the WTO - Inter-Parliamentary Union; Inter-Parliamentary Union
Contents include: Annoted agenda of the session -- Programme of the session -- Inaugural ceremony -- Outcome document -- Hearing with the WTO Director-general, Mr. Pascal Lamy -- Dialogue with the senior WTO negotiators -- Debate on substantive theme (A): Looking beyond Doha -- Deabte on substantive theme (B): Can international trade help mitigate climate change? -- Interactive panel discussion. Defusing the threat of conflicts over food and energy through trade -- Interactive panel discussion. Trade in the era of digital revolution -- Guidelines for relations between governments and parliaments on international trade issues -- Rules of procedure of the Parliamentary conference on the WTO, as amended on 12 September 2008 -- Participation -- Composition of the steering committee -- Acronyms.